Human monocyte colony-stimulating factor stimulates the gene expression of monocyte chemotactic protein-1 and increases the adhesion of monocytes to endothelial monolayers. - Shyy, Y J (1993)
The stimulation of the human umbilical vein endothelial cell (HUVEC) with recombinant human monocyte-derived colony-stimulating factor (MCSF) increased the gene expression of monocyte chemotactic protein (MCP-1). Northern blot analysis indicated that 50 U/ml of MCSF is the optimal concentration for this effect. The elevation of MCP-1 mRNA started as early as 1 h after stimulation and was maintained for at least 8 h. An increased MCP-1 level in MCSF-treated HUVEC was also demonstrated at the protein level by immunocytochemical staining using a polyclonal MCP-1-specific antibody. HUVEC activated by 50 U/ml of MCSF for 5 h showed a stronger immunofluorescence staining than control cells. Micropipette separation of THP-1 monocytes from HUVEC showed that the activation of both THP-1 and endothelium by MCSF led to an increase in the separation force by more than three times (36.2 +/- 6.7 x 10(-4) vs. 9.6 +/- 3.6 x 10(-4) dyn). An increased adhesiveness was also observed after MCSF activation of peripheral blood monocytes and HUVEC (16.7 +/- 2.7 x 10(-4) vs. 5.2 +/- 0.9 x 10(-4) dyn). The increased adhesive force in both systems was blocked by the use of anti-MCP-1 (5.5 +/- 0.8 x 10(-4) and 6.8 +/- 1.1 x 10(-4) dyn). Similar results were obtained in experiments in which only HUVEC, but not monocytes, were activated by MCSF. This increased adhesion of untreated monocytes to MCSF-activated HUVEC was also blocked by the addition of anti-MCP-1. In contrast, experiments in which only THP-1 or peripheral blood monocytes, but not HUVEC, were treated with MCSF did not show a significant increase of adhesion between these cells. These results indicate that MCSF augments monocyte-endothelium interaction primarily by its action on the endothelial cell and that this function is probably mediated through an increased expression of MCP-1. The MCSF/MCP-1-dependent adhesive mechanism might be operative in the arterial wall in vivo to lead to the trapping of the infiltrated monocyte-macrophage in the subendothelial space during atherogenesis.